The use of oral contraceptive before pregnancy and breastfeeding duration: A cross-sectional study with retrospective ascertainment - Soto-Ramírez, Nelís (BioMed Central, 2008)
BACKGROUND: Various studies have identified risk factors associated with decreased breastfeeding duration. The aim of this study was to investigate whether there is an association between oral contraceptive (OC) use before pregnancy and breastfeeding duration. METHODS: In 1994/95, as part of a 3-year epidemiologic follow-up study of school children, reproductive interviews were conducted with their mothers. The study population consists of 663 women residing in Hesse, Central Germany; 575 provided information on their reproductive history. The interview included retrospective ascertainment of OC use, its timing before pregnancy, and duration of breastfeeding. To estimate its effect on duration of breastfeeding, survival analysis was applied controlling for maternal age, socio-demographic characteristics, smoking during pregnancy, age at menarche, planning of the pregnancy and birth order. Hazard ratios and median breastfeeding duration were estimated. RESULTS: The mean age of the women at delivery was 27.3 years. Among participants, 34.9% had high school education or less, 10.4% had more than 2 children, and 30.1% smoked during pregnancy. In total, oral contraceptive use in the 12 months before conception was reported by 40.4% of the women, within 3 months of conception by 18.4%. 81.4% (468/575) of women initiated breastfeeding. Compared to those who did not use OC in the 12 months preceding pregnancy, mothers who used OC during the 3 months before conception had a shorter duration of breastfeeding (HR = 1.29; 95% CI: 1.03, 1.61), as did mothers who stopped OC use 4–12 months before conception (HR = 1.27, 95% CI: 1.02, 1.58). Smoking during pregnancy and lower education were also significantly associated with shorter duration of breastfeeding. CONCLUSION: The results suggest that OC use during the 12 months prior to conception may affect breastfeeding duration. These findings may be due to the endocrine disrupting effect of OC. Alternatively, both OC use and shorter duration of breastfeeding may represent lifestyle-related conditions.